Relationship Between Pregnant Women's Diet With The Event Of Chronic Energy Lack - Novi Indrayani; Siska Puspita Sari; Vio Nita; Karl Heinrich Papua Rumagesan (Science Midwifery, 2022)
Based on a report from the Lany Jaya District Health Office in December 2020, there were 161 pregnant women, 9 of whom experienced SEZ with 1 stillbirth. SEZs in Lanny Jaya Regency can be seen based on the patterns of people's daily lives. The people of Lanny Jaya consume sweet potatoes as their main source of carbohydrates, while most of the protein is obtained from vegetables. The purpose of the study was to determine the relationship between the diet of pregnant women and the incidence of chronic energy deficiency. Methods This research uses quantitative with cross sectional design, observational approach, or data collection. The research subjects are pregnant women with chronic energy deficiency and normal pregnant women. The results of this study are that there is a relationship between diet and the incidence of chronic energy deficiency pregnant women in Tiom District, Lanny Jaya, Papua with a p value of 0.03. The conclusion is that there is a significant relationship between diet and the incidence of chronic energy deficiency in pregnant women.